The Behaviour of Economic Agent in Islam - al Hakim, Muhammad Hanif (El-Barka: Journal of Islamic Economics and Business, 2019)
Abstract: Some notable economists believe that Economics is of normative science, which always focuses on the 'what should be' statement. Therefore it is included in the science of ethics, considering that it discusses an attitude of an individual in economic activity. Unfortunately, modern economics born from the womb of Western Civilization was influenced by Utilitarianism which is undoubtedly contradictary to Islam. This certainly will create problems in the future for Muslims, especially in economic activities both on an individual and social scale. This article will discuss how the behavior of an economic agent should be viewed by Islam. This research is qualitative in nature, using the methos of literature survey. The results of the study show that the correct understanding of Islam, the worldview of Islam, and the true nature of human beings and their actions will keep Muslim behavior as an economic agent from being trapped into un-Islamic behavior in economic activities. الملخص: اعتقد بعض الاقتصاديين البارزين أن الاقتصاد هو نوع من العلوم المعيارية، والذي يركز دائمًا على عبارة "ما يجب أن يكون". فمن ثم هو من علم الأخلاق، معتبرا أنه يناقش كيف يتصرف الشخص في النشاط الاقتصادي. لكن لسوء الحظ، تأثرت الاقتصاد الحديث المولود من رحم الحضارة الغربية بالنفعية التي تناقضت الإسلام بلا شك. سيؤدي هذا خلق مشاكل للمسلمين في المستقبل خاصة في الأنشطة الاقتصادية سواء على المستوى الفردي أو الاجتماعي. يناقش هذا المقال كيف يكون موقف الوكيل الاقتصادي وفقًا للإسلام. هذا البحث هو نوعي في الطبيعة ، وذلك باستخدام منهجية مسح الأدب ومراجعته. تظهر نتائج الدراسة أن الفهم الصحيح للإسلام، ورؤية الإسلام للوجود، والطبيعة الحقيقية للبشر وأفعالهم سوف تبقي سلوك المسلمين كعوامل اقتصادية من الوقوع في سلوك غير إسلامي في الأنشطة الاقتصادية. Abstrak; Beberapa ekonom terkemuka menyakini bahwa Ilmu Ekonomi merupakan jenis ilmu normatif, yang selalu fokus kepada pernyataan ‘apa yang seharusnya’. Oleh karena itu ia termasuk ilmu etika, mengingat ia membahas bagaimana sikap seorang dalam beraktifitas ekonomi. Namun sayangnya, Ilmu Ekonomi modern yang lahir dari rahim Peradaban Barat ini dipengaruhi paham Utilitarisme yang tidak diragukan lagi bertentangan dengan Islam. Hal ini tentu akan melahirkan masalah dikemudian hari bagi umat Islam khususnya dalam aktivitas ekonomi baik dalam skala individu maupun sosial. Artikel ini akan membahas bagaimana seharusnya perilaku seorang agen ekonomi dipandang oleh agama Islam. Penelitian ini bersifat kualitatif, dengan menggunakan metodologi survei literatur. Hasil penelitian menunjukkan kesimpulan bahwa pemahaman yang benar tentang Agama Islam, pandangan dunia Islam, dan sifat asli manusia dan perbuatannya akan menjaga perilaku Muslim sebagai agen ekonomi dari terjebak kedalam perilaku yang tidak Islami dalam beraktifitas ekonomi.